Early apoptotic response in kidney after 177Lu-octreotate administration with or without potential radioprotector α1-microglobulin - Ytterbrink, Charlotte; Simonsson, Klara; Shubbar, Emman; Gram, Magnus ; 0000-0002-5880-2925; Helou, Khalil; Forssell-Aronsson, Eva (Radiation Protection Dosimetry, 2025)
The antioxidant α1-microglobulin (A1M) has been suggested as kidney protector during 177Lu-octreotate treatment. The aim of this work was to evaluate apoptotic-related transcript expression in kidney cortex and medulla following injection of 177Lu-octreotate and/or A1M. Mice were injected with 177Lu-octreotate, A1M, or 177Lu-octreotate + A1M. Control groups received PBS or vehicle solution. Animals were killed after 24 hours or 7 d. mRNA was isolated from kidney medulla and cortex. Expression of 84 apoptosis-related genes was assessed by q-PCR. Gene expression profiles in kidney cortex were generally similar in the 177Lu-octreotate and 177Lu-octreotate + A1M groups. This was also seen in kidney medulla at 24 hours, but at 7 d anti-apoptotic response of A1M was observed. Altogether, 177Lu-octreotate exposure induced pro-apoptotic response (e.g. Apaf1, Bax, and Tnfrsf10b genes) in kidney medulla and cortex. A1M co-administration did not inhibit pro-apoptotic response in kidney cortex, while A1M initiated pro-survival mechanisms in kidney medulla.